FutureDeck - Walz, Steffen P (gerenwa GmbH, 2015)
1. Research Background The FutureDeck (FD) is, in brief and simply, a creative work in the form of a set of print cards to tell stories from the future. As a novel type of foresight tool for an age of digital transformation, which brings forth e.g. unexpected market convergences (Maier and Renz 2015), the FD plafully provides answers to the player on how play mechanics for how to use and combine the cards can produce knowledge about the uncertainties that come with society’s digital transformation. As such, FD produces social, enjoyable ideation sessions around our technologized futures, whilst employing low-technological means. It sits well within the tradition of foresight-oriented, so-called method cards and decks—see, for example, the Drivers of Change cards (Arup 2009)— yet presents a unique, creative approach to inspire entrepreneurial, out-of-the-box, critical, reflective foresight: to help achieve this for the players, the FD uses what can be considered „disruptive play“ to create disruptive ideas. For example, one way to play with the FD challenges players to co-invent a future TV Show format, by randomly mingling two of Australia's economic growth areas (of which there are more than 20, including a blank growth card for one's own idea), and by involving a key digital technology, e.g. 3D Bioprinting; then, this new TV show will have to suffer impacts (incl. silly ones such as "Zombies!"), the outcome which will have to stand against an Ethics card, and lastly, might not be defendable once a superpower card such as "Parallel Universe" will be drawn. 2. Research Contribution The FD, as a form of research-through-design, builds on as well as integrates a number of research outcomes, data as well as philosophical writing. For the current deck to shape up, and for the basic rule-sets to be created, methods from Game Design, such as iterative prototyping and playtesting, were used. Following details for each of the deck’s card categories: • Growth Cards have been derived from Deloitte's study "Positioning for Prosperity? Catching the next wave" as part of their Building the Lucky Country study series, in which Australia's future economic growth sectors have been identified (Deloitte 2014). • Technology Cards are based on Online sources such as www.haxlr8r.com as well as on technology foresight research, such as Gartner's Hype Cycles, see www.gartner.com. • Impact Cards reflect human-made and natural impacts, both positive and negative. • Ethics Cards translate different notions of virtues, as outlined in texts by e.g. Plato, Aristotle, Cicero, Laozi, Paddy Roe and Sebastian Deterding’s talk on Ethics in Interaction Design (Deterding 2014). • Superpower Cards incorporate ideas from science fiction, such as "Immortality" or "Telekinesis." • Objectives Cards have been derived by way of creative ideation and by way of playtesting the FD. The FD pushes for players to converge Australian economic growth sectors with key technologies and other phenomena. As such, by principle, the FD breeds interdisciplinary foresight. As a design artifact, the FD sits at the intersection of –and seems to be interesting to– a diverse set of fields, including Game and Behavioral Design; Foresight; Strategic Innovation; Career Counseling and Assessment; Learning and Teaching etc. 3. Research Significance The FD comes in a "Classic" edition of 126 cards, but has also been customized to address specific audience requirements, by way of tailored FD editions featuring specifically designed cards. Ever since its publication, the FutureDeck has been played in a great variety of settings, from public, free-of- charge events, life on stage, to workshops with national and international clients, including Deloitte Centre for the Edge Australia / USA; Code for Australia; the Australian Trade and Investment Commission (Austrade); the Department of Education and Training Victoria; Daimler (DE); the University of St Gallen's Executive School (CH); etc. Via the website playfuturedeck.com, circa 500 copies of the FutureDeck have been sold since December of 2015. Additionally, via direct bulk orders, another 500, customized copies are in circulation. The FutureDeck has been used in hundreds of workshops, with national and international organizations including Daimler, SAP and Deloitte and Deloitte’s clients, played by an estimated 20,000 players. Lastly, the FutureDeck was a finalist in the Victorian Premier's Design Award in 2015. The FutureDeck's publisher and distributor is gerenwa – All About Connecting The Dots, a small design consultancy and software development company for the age of digital convergences, based in Karlsruhe, Germany.